Advocating for the right to science: An interview with Prof. Helle Porsdam - Porsdam, Helle (Journal of Integrative and Innovative Humanities, 2022)
Helle Porsdam is Professor of Law and Humanities at the Centre for Interdisciplinary Studies of Law at the University of Copenhagen, Denmark. She also holds a UNESCO Chair in Cultural Rights at the University of Copenhagen. In her academic career, Prof. Porsdam has moved from literary studies, to history and then eventually to the cultural role of law, law and humanities, and human rights. Her two latest books deal with the right to science – one of the cultural rights mentioned in both the 1948 Universal Declaration of Human Rights and the 1966 International Covenant on Economic, Social and Cultural Rights (Porsdam & Mann 2021; Porsdam 2022).